Diagnosis of Polycystic Ovary Syndrome using Free Testosterone levels via Surface Enhanced Raman Spectroscopy Induced by Gold Nanostar - Imran, Ruaa E.; Faris, Rawaa A. (Iraqi Journal of Laser, 2024)
Background: Polycystic ovary syndrome (PCOS) manifests as anovulation, oligomenorrhea, and hyperandrogenism in women of reproductive age, affecting around 5-10% of this population. There is a pressing want for a rapid, inexpensive, and uncomplicated approach to qualitatively and quantitatively detect free testosterone in patients with Polycystic Ovary Syndrome (PCOS).Materials and methods: This study utilized surface-enhanced Raman spectroscopy (SERS) coupled with gold nano star (GNS) to amplify the optical signal to detect serum-free testosterone in PCOS patients. The study comprised 56 PCOS women age range (17-45years) who were sent from different governorates to the Baghdad Medical City.Results: Highly resolved and high-quality surface-enhanced Raman scattering (SERS) spectra were obtained for free testosterone adsorbed on a substrate. These spectra exhibited characteristic bands of free testosterone and allowed for the detection of low levels (1.7 nM/mL), with an enhancement factor (EF) of 59 *105.Conclusions: Based on the current knowledge this paper represents the pioneering effort to ascertain the concentration of free testosterone with the SERS technique. It is possible to efficiently early detection of PCOS by measuring the very low concentration of serum-free testosterone in a low-cost technique. e Size